Genetic and Molecular Epidemiology of Multiple Myeloma - Lentzsch, Suzanne; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This state-of-the-art book is written by a group of international experts to provide insight into the newest breakthroughs from basic pathogenesis to clinical aspects of multiple myeloma. The book provides a comprehensive overview of the genetic and molecular epidemiology of multiple myeloma in order to get a more refined and conclusive understanding of this disease.  Areas, which are covered include the characterization of different myeloma entities by genomics and proteomics, notch signaling and targeting protein translation as a new treatment for multiple myeloma, cell cycle control of plasma cell differentiation, the role of bone disease in the pathogenesis of multiple myeloma as well as the molecular interaction of multiple myeloma with a microenvironment. Genetic and Molecular Epidemiology of Multiple Myeloma is a valuable resource for cancer researchers, medical, surgical, and radiation oncologists.
Preface -- Genetics of Multiple Myeloma -- Gene expression signature in MGUS and multiple myeloma -- Cap-Dependent Protein Translation Initiation in Multiple Myeloma: an Attractive Target for Therapy -- IRES-dependent, CAP-independent translation in Multiple Myeloma -- Epigenetic gene silencing as a new target for multiple myeloma -- Role of Bone Disease in the Pathogenesis of Multiple Myeloma -- Index.
Keywords: Cancer research; Cell biology; Human genetics; Cancer Research; Cell Biology; Human Genetics